PENGARUH EPS, PER DAN PBV TERHADAP HARGA SAHAM (PADA PERUSAHAAN SEKTOR MANUFAKTUR YANG TERDAFTAR JII) - Permatasari, Ninda Putri; Isharijadi, Isharijadi; Wihartanti, Liana Vivin (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2020)
The purpose of this study was to determine the effect of EPS, PER and PBV on stock prices. The research sample is 8 manufacturing sector companies registered in the Jakarta Islamic Index in 2016-2018. The type of data is quantitative descriptive using a purposive sampling method for sampling. The data analysis technique to test the hypothesis is multiple linear analysis. The results of the study show that EPS and PBV have a significant positive effect on stock prices, PER has a significant negative effect on stock prices. Because, when analyzing there are several company stock prices rising and profits falling a share. The three EPS, PER and PBV variables have an effect on the stock price simultaneously.